Green office management standard in Mahidol University, Thailand - Sayam Aroonsrimorakot (2019)
© 2018 Universiti Putra Malaysia Press. Green Office is an environmental service for offices and in the recent decades, there is a growing concern about the green office management standard in Thailand with its goal as to create a healthy environment, conserve energy, and reduce pollution by reducing carbon dioxide emissions and offices' ecological footprint. With its help, workplaces are able to reduce their burden on the environment, achieve savings and slow down climate change. It is a practical environmental management system for the offices applicable both in a small or large organization, in private companies or the public sector, easy to implement in urban environments and which help in reducing the ecological footprint and greenhouse gas emissions of the office. This paper describes the purpose, principles, features, procedure for setting up, and management of green office standard in Thailand with the main aim of describing the growing importance of green office due to the impact of climate change. It also aims to promote sustainable practices, apply the Green Office principles in organizations and offices so as to reduce the emission released by activities in the offices. The study was carried out through EDFR procedure by selecting a panel of 17 experts to get the detail data and opinion for management of green office in Thailand. The study results or contributes to the rationalization and mitigation of climate change through following the adaptive green office strategies and it brings out the importance of human factors and behavioral practices at workplaces and offices.